Prenatal Diagnosis and Postnatal Outcome of Fetuses with Pulmonary Atresia and Ventricular Septal Defect - Gottschalk, Ingo; Strizek, Brigitte; Jehle, Christel; Stressig, Rüdiger; Herberg, Ulrike; Breuer, Johannes; Brockmeier, Konrad; Hellmund, Astrid; Geipel, Annegret; Gembruch, Ulrich; Berg, Christoph (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose To assess the intrauterine course, associated conditions and postnatal outcome of fetuses with pulmonary atresia with ventricular septal defect (PAVSD).Methods All cases of PAVSD diagnosed prenatally over a period of 10 years with a minimum follow-up of 6.5 years were retrospectively collected in 3 tertiary referral centers.Results 50 cases of PAVSD were diagnosed prenatally. 44.0 % of fetuses had isolated PAVSD, 4.0 % had associated cardiac anomalies, 10.0 % had extra-cardiac anomalies, 38.0 % had chromosomal anomalies, 4.0 % had non-chromosomal syndromes. Among the 32 liveborn children, 56.3 % had reverse flow in the patent arterial duct, 25.0 % had major aortopulmonary collateral arteries (MAPCAs) with ductal agenesis and 18.7 % had a double supply. 17 pregnancies were terminated (34.0 %), there was 1 intrauterine fetal death (2.0 %), 1 neonatal death (2.0 %), and 6 deaths (12.0 %) in infancy. 25 of 30 (83.3 %) liveborn children with an intention to treat were alive at the latest follow-up. The mean follow-up among survivors was 10.0 years (range 6.5–15.1). 56.0 % of infants underwent staged repair, 44.0 % had one-stage complete repair. After exclusion of infants with additional chromosomal or syndromal anomalies, 88.9 % were healthy, and 11.1 % had mild limitations. The presence of MAPCAs did not differ significantly between survivors and non-survivors (p = 0.360), between one-stage or staged repair (p = 0.656) and healthy and impaired infants (p = 0.319).Conclusion The prognosis in cases without chromosomal or syndromal anomalies is good. MAPCAs did not influence prognosis or postoperative health. The incidence of repeat interventions due to recurrent stenoses is significantly higher after staged compared with single-stage repair.
Keywords: ventricular septal defect; congenital heart defect; prenatal diagnosis; fetus; pulmonary atresia